Taboes & Rituelen. (Turnhout : De Warande, 1983)
Daems, Walter ; Merk, M.E. ; Merz, Mario ; Beuys, Joseph ; Bervoets, Fred ; Czymkowicz, Ch. ; Rops, Felicien ; Lattier, G. ; Van Straeten, H. ; Klossowski, Pierre ; Selen, Max ; Cardena, M. ; etc.
Taboes & Rituelen, De Warande, Turnhout, 1 - 22 mei 1983
Nederlands
kunstcatalogus